Try Bravery for a Change: Supporting Indigenous Health Training and Development in Canadian Universities - Chantelle Richmond (aboriginal policy studies, 2018)
The persistence of egregious inequities signals that we are at a critical juncture regarding the health of Canada’s Indigenous peoples. Now is the time to seriously reflect on the relationships between Indigenous realities, public policy, and the role of Indigenous research environments therein. Addressing the complexity of contemporary Indigenous health inequity requires a fundamental reorientation in the ways we conduct and think about research. This commentary explores the transition currently taking place in Indigenous health training and development in Canadian universities, with a focus on Ontario’s Indigenous Mentorship Network. At the heart of the Ontario Network is the Anishinabe philosophy Mno Nimkodadding Geegi (“We Are All Connected”). In our attempts to address Indigenous health inequality in Canada, we take the perspective that the most important answers will come when we take the time to listen to Indigenous communities. This commentary closes with a discussion on bravery. Just as Indigenous scholars push to make space for their scholarship within the university environments, so too must our institutions have the bravery needed to address the structural changes required to foster that success.